Whole Cell Sensing Systems I Reporter Cells and Devices - Belkin, Shimshon; Gu, Man Bock.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Reporter cells: - Yeast Based Sensors by Mifumi Shimomura-Shimizu and Isao Karube - Mammalian Cell-Based Sensor Systems by Pratik Banerjee, Briana Franz, and Arun K. Bhunia - Fluorescent and Bioluminescent Cell-Based Sensors: Strategies for Their Preservation by Amol Date, Patrizia Pasini, and Sylvia Daunert - Electrochemical Cell-Based Sensors by Eliora Z. Ron and Judith Rishpon - Microbial Cell Arrays by Tal Elad, Jin Hyung Lee, Man Bock Gu, and Shimshon Belkin Devices: - Surface Functionalization for Protein and Cell Patterning by Pascal Colpo , Ana Ruiz , Laura Ceriotti , and François Rossi - Fiber-Optic Based Cell Sensors by Evgeni Eltzov and Robert S. Marks - Electronic Interfacing with Living Cells by James T. Fleming - On-Chip Detection of Cellular Activity by R. Almog , R. Daniel , S. Vernick , A. Ron , H. Ben-Yoav, and Y. Shacham-Diamand
Keywords: Chemistry; Analytical biochemistry; Biotechnology; Cytology; Cytology -- Research_xMethodology.; Chemistry; Biotechnology; Cell Biology; Biological Techniques; Analytical Chemistry